Appreciating formal and informal knowledge transfer practices within creative festival organizations. Issue 1 (8th February 2016) - Stadler, Raphaela; Fullagar, Simone
Abstract : Purpose: – Problem-solving approaches to research have dominated the not-for-profit festival management field. Little attention has been paid to how festival organizations successfully create cultures where knowledge transfer is practised within the high intensity of a festival life cycle. Drawing upon insights from social practice theory and appreciative inquiry (AI), the purpose of this paper is to offer a different conceptual approach to understanding how knowledge transfer "works" as an organizational practice to produce a collaborative festival culture. Design/methodology/approach: – This paper draws upon an ethnographic case study with the highly acclaimed Queensland Music Festival organization in Australia. The research questions and methods were framed around an appreciative approach that identified formal and informal practices that " worked " rather than a conventional problem-focused analysis. Findings: – This research focused on appreciating the cultural context that shaped the interrelationships between formal and informal knowledge transfer practices that enabled trust and collaboration. A range of knowledge transfer practices was identified that contributed to the creation of a shared festival ethos and the on-going sustainability of the festival vision. Practical implications: – The not-for-profit sector brings numerous challenges for festival organizations, and there is a need to appreciate how collaborative and creative knowledge transfer can occur formally and informally. Festival organizers can benefit from understanding the relational and practice dimensions of knowledge management as they are performed within specific organizational contexts. Originality/value: – An appreciative understanding of knowledge transfer practices has not yet been applied to not-for-profit festival organizations, where problem-solving approaches dominate the field.